A local city to a creative city: an examination of Taichung, Taiwan. (13th September 2010) - Liu, Li-Wei; Ko, Pei-Yin
The creative city has become a worldwide subject in urban studies. Cultural industries now serve as the motor of urban creativity and regeneration. But, the construction of a creative city is not an easy task and requires a long period of policy manipulation. Many cities thus manage to 'become' a creative city. This paper calls these cities 'creationalising cities'. This term carries a twofold meaning: one is to succeed in becoming a creative city; the other involves building a creative urban environment. As the third largest city in Taiwan, Taichung strives to become a creative city. Important urban development, cultural facilities, and amenities are under construction. However, Taichung's endeavour to be a creative city seems to fall in the category of place marketing and consumption. According to the quantitative analysis, Taichung needs a more solid cultural foundation building to promote itself from a local city to a creative city.